Impact of diverse cropping patterns on greenhouse gas emissions: assessing energy use efficiency in Rangpur District, Bangladesh - Md. Arifur Rahaman; Alanuzzaman Kurishi, A.S.M.; Cheesman, Stephanie; Hossain, Md. Khaled; Hussain, Afzal; Ferdous, Zannatul; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
Bangladesh relies heavily on rice-based cropping systems to maintain food security. Additionally, crop diversification, which also contribute to enhance agricultural productivity and profitability in a nation with a high population density and scarce arable land. However, greenhouse gas emissions from the agricultural sector is remain unclear. On-farm research trials briefly summarize the results of greenhouse gas emissions from a diversified cropping systems after one full cropping cycle. This trial was conducted in the Chargonai and Shibdeb villages of the Rangpur district, addressing total global warming potential, total energy use, and emissions intensity, which are crucial for achieving TAFSSA’s goals. Therefore, the trial aims to emphasize climate change effects to identify strategies to mitigate greenhouse gas emissions from agricultural land.